Interaksi Sosial dalam Novel Romansa Kota Bandung Karya Kezia Olivia - Nursila, Nursila; Rahayu, Sri (UIR Press, 2023)
This study aims to analyze, describe, and explain the forms of social interaction contained in the novel Romance Kota Bandung by Kezia Olivia. This research uses a qualitative approach with descriptive methods. The data from this study are text or quotations in the form of dialogues, monologues and forms of social interaction contained in the novel Romance Kota Bandung by Kezia Olivia. The data source for this research is the novel Romance of the City of Bandung by Kezia Olivia. The Bandung City Romance Novel by data classification contained in the Bandung City Romance novel by Kezia Olivia, namely forms of social interaction. The results of this study found as many as 118 data. Associative forms of social interaction found as many as 42 data. Associative forms of accommodation 33 data, associative cooperation 3 data, and associative assimilation 4 data. While social interaction in the form of dissociative data found as many as 76. Dissociative contradiction 39 data, dissociative competition 3 data, and dissociative conflict 31 data.